An optimal configuration for hybrid SOFC, gas turbine, and Proton Exchange Membrane Electrolyzer using a developed Aquila Optimizer. (15th February 2022) - Wang, Shicheng; Ma, Jiawei; Li, Wei; Khayatnezhad, Majid; Rouyendegh, Babak Daneshvar
Abstract: In this research, a technical, economic and environmental analysis has been proposed to a Hybrid Solid Oxide Fuel Cell (SOFC) system-based hybrid system including biomass, gas turbine, and Proton Exchange Membrane Electrolyzer. A multi-objective optimization technique has been utilized to improve the overall product cost and the exergy effectiveness based on a developed version of Aquila Optimizer (DAO). The main idea of using the developed version is to improve the accuracy and the precision of the original Aquila optimizer. The system is then authenticated in terms of energy/exergy effectiveness, and energy-economic efficiency. The achievements indicate that employing the optimization algorithm for different configurations provided satisfying results for the system. Highlights: A hybrid of SOFC with Gas turbine can be used to decrease the need for combustion. The hybrid system is optimized by a new improved Multi-objective Aquila Optimizer. Technical, economic and environmental analysis are done on the proposed system.